Shopping Our Way to Safety : How We Changed from Protecting the Environment to Protecting Ourselves - Szasz, Andrew, 1947- (Book collections on Project MUSE., 2007)
Many Americans today rightly fear that they are exposed to toxins in their environment. Yet we have responded not by pushing for governmental regulation, but instead by shopping. Andrew Szasz examines this phenomenon and argues that when consumers believe that they are buying a defense from hazards, they feel less urgency to fix them. To achieve real protection, he concludes, we must give up individual solutions and together seek reform.